Pathogenicity and immune modulation of porcine circovirus 3 - Chen, Dengjin; Zhang, Lei; Xu, Shengkui (Frontiers in Veterinary Science, 2023)
Porcine circoviruses (PCVs) are members of the genus Circovirus of the family Circoviridae, and four species of PCVs have been discovered and named PCV1-PCV4, respectively. With the first report of PCV3 in America in 2016, the pathogenic variant was found to be associated with various clinical features, called porcine circovirus associated disease (PCVAD), including multisystemic inflammation, porcine dermatitis and nephropathy syndrome (PDNS), reproductive disorders, respiratory or digestive disorders. Increasing experimental data have shown that PCV3 is widespread around the world, but the failure of virus isolation and propagation has put obstacles in the way of PCV3 research. Moreover, a large number of reports demonstrate that PCV3 usually co-infects with other pathogens in pigs. Thus, whether PCV3 alone causes clinical manifestations needs to be fully discussed.In addition, the host cell immune response was activated during PCV3 infection, and PCV3-encoded proteins may regulate immune responses to facilitate its replication.An in-depth understanding of PCV3 pathogenesis and immune regulation strategies is critical for PCVAD prevention. In this review, the advances in pathogenicity and innate immune modulation of PCV3 were summarized, which could deepen the understanding of this virus and PCV3-related diseases.